Method for preparing cesium-lead-bromine quantum dots by coating perovskite precursor in situ
Through the method of SiO2 in situ coating perovskite precursor, the problem of easy decomposition of perovskite quantum dots in harsh environments is solved, the stability and particle size are improved, and the use of toxic reagents is avoided, which meets the actual situation. Requirements for application scenarios.
Patent Information
- Application Number
- CN202411166833.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2025-02-18
AI Technical Summary
Existing perovskite quantum dots are easy to decompose in wet, heat, oxygen-rich and light environments, resulting in a decrease in fluorescence efficiency. The commonly used coating methods have the problem of using toxic organic reagents and particle agglomeration, which is difficult to meet the needs of practical application scenarios. .
The method of SiO2 in situ coated perovskite precursor is adopted to dissolve the precursor of cesium lead bromine quantum dots in water and react with ethyl orthosilicate and anti-sintering agent in ethanol of ammonia water to form a uniform coating of SiO2. The quantum dot precursor is then sintered at high temperature to remove the anti-sintering agent and obtain SiO2 in situ coated cesium lead bromine perovskite quantum dots.
The stability of cesium lead bromine quantum dots has been improved, with a particle size of less than 3μm, and the particle size of some particles can reach the submicron level. The sample has excellent light stability performance, avoiding the environmental and health risks of using toxic organic reagents.
Smart Images

Figure CN119463866A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of quantum dot luminescent materials, and in particular relates to a method for preparing cesium lead bromine quantum dots by in-situ coating of perovskite precursors. Background Art
[0002] As a new type of semiconductor light-emitting material, CsPbX3 (X = Cl, Br, I) perovskite quantum dots have the characteristics of high carrier mobility, narrow spectral bandwidth, wide color gamut, high photoluminescence quantum yield, and low cost, and have great commercial application potential in the fields of display, LED, solar cell, photodetector, laser, etc. However, due to strong ion mobility and unstable structure, CsPbX3 perovskite quantum dots are easy to decompose in wet, hot, oxygen-rich and light environments, resulting in a sharp drop in its fluorescence efficiency and even photoquenching.
[0003] Coating quantum dots with inorganic oxides is one of the effective strategies to improve their stability. Common coating methods include: 1. Using molecular sieve as a porous carrier, mixing cesium lead halide precursor with it, and then using a solid phase method to anneal at high temperature so that the perovskite quantum dots are encapsulated in the pores of the molecular sieve (CN 113501540 A, CN 115806814 A, InfoMat. 2023, 5(7): e12417); 2. Preparing perovskite quantum dots by hot injection, ligand-assisted co-precipitation, etc., and then adding a silicon source for hydrolysis and coating (CN 114574201 A, CN 116004228 A); 3. Mixing the cesium lead halide precursor raw material with a silicon source, and then injecting toluene at room temperature or reacting under microwave to obtain a loaded or coated product (CN112961675 A, CN 108298577 A, CN 108531173 A). In addition, patent CN 114806561A discloses a method for synthesizing a stable perovskite with dual protection of SiO2 and PbSO4. The method first dissolves cesium halide and lead halide in dimethyl sulfoxide, then adds a silicon source, and calcines the precipitate obtained after catalytic hydrolysis at 350-500°C to obtain the product.
[0004] Considering that the toxic organic reagents used in the liquid phase method for preparing quantum dots can cause harm to the environment and human body, and the solid phase method easily causes particle agglomeration during the annealing process, it is difficult to adapt to the demand for small particle size in some practical application scenarios (such as inkjet printing). Developing a preparation method that does not use toxic organic reagents to obtain perovskite quantum dots with small particle size and good stability will have attractive market prospects. Summary of the invention
[0005] The object of the present invention is to provide a method for preparing cesium lead bromine quantum dots by in-situ coating of perovskite precursors, which method does not use toxic organic reagents such as benzene, dimethyl sulfoxide or N,N-dimethylformamide, and the obtained sample has excellent photostability, and its particle size is less than 3μm, and the particle size of some particles can reach submicron level.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] A method for preparing cesium lead bromine quantum dots by in-situ coating of a perovskite precursor, the method comprising the following steps:
[0008] (1) mixing and dissolving the precursors for preparing cesium lead bromine quantum dots in water to obtain a solution A;
[0009] (2) mixing solution A with ethanol containing aqueous ammonia under stirring to obtain solution B;
[0010] (3) under continuous stirring, adding tetraethyl orthosilicate and an anti-sintering agent to solution B, and after the reaction is completed, concentrating and drying the resulting mixed solution to obtain a quantum dot precursor powder in situ coated with SiO2;
[0011] (4) The obtained SiO2 in-situ coated quantum dot precursor powder is treated at high temperature in a muffle furnace, and the anti-sintering agent is removed after cooling to obtain SiO2 in-situ coated cesium lead bromine perovskite quantum dots.
[0012] In the above, cesium lead bromine perovskite quantum dots refer to CsPbBr3 structure, CsPbBr y I 3-y The perovskite quantum dots have a structure or a FACsPbX structure (X represents bromine or a mixed halogen containing bromine). At the same time, according to the different structural formulas of cesium lead bromine perovskite quantum dots, those skilled in the art have the motivation and ability to select suitable precursor types of cesium lead bromine quantum dots for preparation. All of the above should be included in the protection scope of the present invention.
[0013] Furthermore, the precursors of the cesium lead bromine quantum dots in step (1) are CsBr and PbBr2;
[0014] Wherein, in the step (1), the molar ratio of CsBr to PbBr2 is 1:1 to 1:1.5, and the total concentration of CsBr and PbBr2 in water is 0.02 to 0.06 mol / L.
[0015] Furthermore, in step (2), the volume ratio of ethanol containing aqueous ammonia to solution A is 5:1 to 10:1, wherein the volume ratio of aqueous ammonia to ethanol is 1:10 to 1:8.
[0016] Furthermore, in step (3), the volume ratio of tetraethyl orthosilicate to solution A is 1:4 to 1:1, and tetraethyl orthosilicate is added dropwise at a dropping rate of 0.08 to 0.2 mL / min.
[0017] Under the catalytic action of ammonia water, ethyl orthosilicate undergoes hydrolysis and cross-linking reactions. In this process, the initial sol particles produced by its hydrolysis will adsorb Cs+, Pb2+ and Br- ions, and the sol formed by subsequent hydrolysis will uniformly coat these adsorbed ions. The purpose of controlling the addition method and addition speed of ethyl orthosilicate is to control its hydrolysis speed and thus control the particle size of the inclusions.
[0018] Furthermore, the anti-sintering agent includes at least one of a liquid anti-sintering agent and a solid anti-sintering agent; specifically:
[0019] The anti-sintering agent is one or more combinations of liquid hexamethyldisilazane, methyltrichlorosilane, dichlorodimethylsilane, n-octadecyldimethylchlorosilane, or solid sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium bicarbonate, sodium carbonate, and potassium carbonate.
[0020] Among them, the liquid anti-sintering agent is a silane coupling agent with a hydrophobic group. Under the catalytic action of ammonia water, these silane coupling agents will form chemical modifications on the surface of the sol inclusion particles, hindering the agglomeration between the inclusion particles and the possibility of cross-linking between the particles through dehydration between the surface hydroxyl groups during the subsequent sintering process. The solid anti-sintering agent mainly forms a physical barrier between the inclusion particles, and is removed after the subsequent high-temperature treatment, thereby ensuring that the inclusion particles will not agglomerate and fuse in large quantities during the sintering process.
[0021] Furthermore, the anti-sintering agent is added all at once. If the anti-sintering agent is in liquid form, it is added at 0.1 to 0.5 times the volume of tetraethyl orthosilicate. If the anti-sintering agent is in solid form, it is added at 0.5 to 5 times the mass of tetraethyl orthosilicate.
[0022] Furthermore, in step (3), the mixed solution is concentrated by atmospheric pressure or reduced pressure distillation, and the drying method is oven drying or freeze drying.
[0023] Furthermore, in step (4), the temperature of the high temperature treatment in the muffle furnace is 350-450°C, the heating rate is 10-20°C / min, the holding time is 5-10min, and the cooling rate is 1-5°C / min.
[0024] Furthermore, the method of removing the anti-sintering agent in step (4) is:
[0025] Liquid anti-sintering agent, the organic part has been removed during high temperature treatment;
[0026] Solid anti-sintering agents are removed by washing and filtering.
[0027] Specifically: if the anti-sintering agent is one or more combinations of hexamethyldisilazane, methyltrichlorosilane, dichlorodimethylsilane or n-octadecyldimethylchlorosilane, the organic part thereof has been removed during high-temperature treatment; if the anti-sintering agent contains one or more combinations of sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium bicarbonate, sodium carbonate and potassium carbonate, it is removed by washing with water and filtering.
[0028] The beneficial effects of the present invention are mainly reflected in:
[0029] (1) The proposed method of preparing cesium lead bromine quantum dots by in-situ coating of perovskite quantum dot precursors with SiO2 can pre-embed and encapsulate the quantum dot precursors and combine them with a solid-phase reaction, so that the subsequently formed cesium lead bromine quantum dots can be uniformly and effectively coated with SiO2, which is beneficial to improving the stability of the quantum dots.
[0030] (2) The method used is simple to operate and does not use toxic organic reagents such as benzene, dimethyl sulfoxide, or N,N-dimethylformamide.
[0031] (3) By introducing an anti-sintering agent during the encapsulation process of the quantum dot precursor to prevent the agglomeration and fusion between the inclusions, the obtained SiO2 in-situ encapsulated cesium lead bromide perovskite quantum dot sample can have a particle size less than 3 μm, and the particle size of some particles can reach submicron level. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 TEM image of the SiO2 in-situ coated cesium lead bromide perovskite quantum dot sample prepared in Example 1;
[0033] Figure 2 The particle size distribution diagram of the SiO2 in-situ coated cesium lead bromine perovskite quantum dot sample prepared in Example 1;
[0034] Figure 3 The fluorescence emission spectrum of the SiO2 in-situ coated cesium lead bromine perovskite quantum dot sample prepared in Example 1;
[0035] Figure 4 These are the photostability test results of the SiO2 in-situ coated cesium lead bromide perovskite quantum dot sample prepared in Example 1. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific implementation methods described herein are only used to explain the present invention and are not used to limit the present invention.
[0037] Embodiment 1:
[0038] 0.213g CsBr and 0.266g PbBr2 were mixed and dissolved in 20mL distilled water to obtain solution A. 10mL ammonia water was added to 90mL anhydrous ethanol, and then solution A was added to the ethanol with ammonia water under stirring to obtain solution B. Under continuous stirring, 5mL of tetraethyl orthosilicate was added dropwise to solution B at a dropping rate of 0.08mL / min. After the addition of tetraethyl orthosilicate was completed, 2.5mL of hexamethyldisilazane was added to the reaction system and the reaction was continued for 6h. After the reaction was completed, the obtained mixed solution was concentrated by vacuum distillation using a rotary evaporator to remove most of the solvent, and then the concentrated solution was dried in an oven at 80°C to obtain a quantum dot precursor powder coated in situ with SiO2. The obtained SiO2 in situ coated quantum dot precursor powder was placed in a ceramic crucible and then placed in a muffle furnace for high temperature treatment. The heating rate was 20°C / min. When the furnace temperature reached 400°C, it was kept warm for 10 minutes and then cooled to room temperature at a rate of 2°C / min to obtain a SiO2 in-situ coated cesium lead bromine perovskite quantum dot sample.
[0039] Figure 1 TEM image of the SiO2 in-situ coated cesium lead bromide perovskite quantum dot sample prepared in Example 1. Figure 1 It can be seen that the quantum dots are uniformly dispersed and wrapped inside the SiO2. The particle size distribution diagram of the SiO2 in-situ coated cesium lead bromide perovskite quantum dot sample prepared in Example 1 ( Figure 2 ) It can be seen that the particle size of the obtained sample is below 3μm, and half of the particles are around 500nm in size. Figure 3 This is the fluorescence emission spectrum of the SiO2 in-situ coated cesium lead bromide perovskite quantum dot sample prepared in Example 1. The fluorescence emission wavelength of the sample is 516nm, the half-peak width is 23nm, and the fluorescence quantum efficiency is 86%. Photostability test results ( Figure 4 ) showed that the fluorescence intensity retention rate of the SiO2 in-situ coated cesium lead bromide perovskite quantum dot sample prepared in Example 1 was 87% after 24 hours of ultraviolet irradiation, and there was almost no attenuation in the first 2 hours, indicating that the sample had good photostability.
[0040] Embodiment 2-4:
[0041] A method for preparing cesium lead bromine quantum dots by in-situ coating of a perovskite precursor, the method comprising the following steps:
[0042] (1) mixing CsBr and PbBr2, precursors for preparing cesium lead bromine quantum dots, in a certain proportion and dissolving them in distilled water to obtain solution A;
[0043] (2) Under stirring, adding solution A to ethanol containing aqueous ammonia to obtain solution B;
[0044] (3) under continuous stirring, adding tetraethyl orthosilicate and an anti-sintering agent to solution B in sequence, and after the reaction is completed, concentrating and drying the resulting mixed solution to obtain a SiO2 in-situ coated quantum dot precursor powder;
[0045] (4) The obtained SiO2 in-situ coated quantum dot precursor powder is treated at high temperature in a muffle furnace, and the anti-sintering agent is removed after cooling to obtain SiO2 in-situ coated cesium lead bromine perovskite quantum dots.
[0046] The raw materials and proportions of each component in each step in Examples 2-4 and Comparative Examples 1-2, the specific parameter conditions, and the results of the prepared SiO2 in-situ coated cesium lead bromide perovskite quantum dot sample are shown in Table 1:
[0047] Table 1: Test scheme of Examples 2-4 and Comparative Examples 1-2
[0048]
[0049] Embodiment 5-9:
[0050] A method for preparing cesium lead bromine quantum dots by in-situ coating of a perovskite precursor, the method comprising the following steps:
[0051] (1) mixing CsBr and PbBr2, precursors for preparing cesium lead bromine quantum dots, in a certain proportion and dissolving them in distilled water to obtain solution A;
[0052] (2) Under stirring, adding solution A to ethanol containing aqueous ammonia to obtain solution B;
[0053] (3) under continuous stirring, adding tetraethyl orthosilicate and an anti-sintering agent to solution B in sequence, and after the reaction is completed, concentrating and drying the resulting mixed solution to obtain a SiO2 in-situ coated quantum dot precursor powder;
[0054] (4) The obtained SiO2 in-situ coated quantum dot precursor powder is treated at high temperature in a muffle furnace, and the anti-sintering agent is removed after cooling to obtain SiO2 in-situ coated cesium lead bromine perovskite quantum dots.
[0055] The raw materials and proportions of each component in each step of Examples 5-9, the specific parameter conditions, and the results of the prepared SiO2 in-situ coated cesium lead bromine perovskite quantum dot sample are shown in Table 2:
[0056] Table 1: Experimental protocols for Examples 5-9
[0057]
[0058]
[0059] The present invention illustrates the detailed preparation method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed preparation method, that is, it does not mean that the present invention must rely on the above-mentioned products and detailed preparation methods to be implemented. It should be clear to those skilled in the art that any improvement of the present invention, the combination or equivalent replacement of the raw materials of the product of the present invention, all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing cesium lead bromine quantum dots by in-situ coating of perovskite precursors, characterized in that: The steps include: (1) dissolving a precursor for preparing cesium lead bromine quantum dots in water to obtain a solution A; (2) mixing solution A with ethanol containing aqueous ammonia to obtain solution B; (3) adding tetraethyl orthosilicate and an anti-sintering agent to solution B, and after the reaction is completed, concentrating and drying the resulting mixed solution to obtain a quantum dot precursor powder in situ coated with SiO2; (4) The obtained SiO2 in-situ coated quantum dot precursor powder is treated at high temperature in a furnace, and the anti-sintering agent is removed after cooling to obtain SiO2 in-situ coated cesium lead bromine perovskite quantum dots.
2. The method for preparing cesium lead bromine quantum dots by in-situ coating of perovskite precursors according to claim 1, characterized in that: The precursors of the cesium lead bromine quantum dots in step (1) are CsBr and PbBr2; Among them, the molar ratio of CsBr and PbBr2 is 1:1 to 1:1.5, and the total concentration of CsBr and PbBr2 in water is 0.02 to 0.06 mol / L.
3. The method for preparing cesium lead bromine quantum dots by in-situ coating of perovskite precursors according to claim 1, characterized in that: In the step (2), the volume ratio of ethanol containing ammonia water to solution A is 5:1 to 10:1, wherein the volume ratio of ammonia water to ethanol is 1:10 to 1:
8.
4. The method for preparing cesium lead bromine quantum dots by in-situ coating of perovskite precursors according to claim 1, characterized in that: In the step (3), the volume ratio of ethyl orthosilicate to solution A is 1:4 to 1:1, and ethyl orthosilicate is added dropwise.
5. The method for preparing cesium lead bromine quantum dots by in-situ coating of perovskite precursors according to claim 4, characterized in that: The dropping rate of the tetraethyl orthosilicate is 0.08-0.2 mL / min.
6. The method for preparing cesium lead bromine quantum dots by in-situ coating of perovskite precursors according to claim 1, characterized in that: The anti-sintering agent includes at least one of a liquid anti-sintering agent and a solid anti-sintering agent; The liquid anti-sintering agent is one or more combinations of liquid hexamethyldisilazane, methyltrichlorosilane, dichlorodimethylsilane, and n-octadecyldimethylchlorosilane; The solid anti-sintering agent is one or more combinations of sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium bicarbonate, sodium carbonate, and potassium carbonate.
7. The method for preparing cesium lead bromine quantum dots by in-situ coating of perovskite precursors according to claim 6, characterized in that: The anti-sintering agent is added in one go; The liquid anti-sintering agent is added at a volume of 0.1 to 0.5 times that of ethyl orthosilicate; The solid anti-sintering agent is added at 0.5 to 5 times the mass of ethyl orthosilicate.
8. The method for preparing cesium lead bromine quantum dots by in-situ coating of perovskite precursors according to claim 1, characterized in that: In the step (3), the mixed solution is concentrated by atmospheric pressure or reduced pressure distillation, and dried by oven drying or freeze drying.
9. The method for preparing cesium lead bromine quantum dots by in-situ coating of perovskite precursors according to claim 1, characterized in that: In the step (4), a muffle furnace is used as the furnace body, the temperature of the muffle furnace high temperature treatment is 350-450°C, the heating rate is 10-20°C / min, the insulation time is 5-10min, and the cooling rate is 1-5°C / min.
10. The method for preparing cesium lead bromine quantum dots by in-situ coating of perovskite precursors according to claim 7, characterized in that: The method of removing the anti-sintering agent in step (4) is: For liquid anti-sintering agents, the organic part has been removed during high-temperature treatment; for solid anti-sintering agents, it is removed by washing and filtering.
Citation Information
Patent Citations
Method for realizing stable coating of perovskite quantum dots by using intermediate sacrificial layer
CN114574201A
Surface modified perovskite quantum dot, preparation method thereof and core-shell structure quantum dot
CN116004228A